Internet addiction in adolescents: the PROTECT program for evidence-based prevention and treatment - Lindenberg, Katajun; Kindt, Sophie; Szász-Janocha, Carolin (Springer, 2020)
Part I: Internet Use Disorders in Adolescents -- Chapter 1. Definition and Diagnostics of Internet Use Disorders -- Chapter 2. Characteristics and Conditions Associated with Internet Use Disorders -- Chapter 3. Etiology of Internet Use Disorders -- Chapter 4. Treatment and Prevention for Adolescents with Internet Use Disorders -- Chapter 5. The PROTECT Intervention -- Part II: The PROTECT Program for Evidence-Based Prevention and Treatment -- Chapter 6. Module 1 – Boredom and Motivational Problems -- Chapter 7. Module 2 – Performance Anxiety and Procrastination -- Chapter 8. Module 3 – Social Anxiety -- Chapter 9. Module 4 – Emotion Regulation. .